Kewenangan Pemerintah Daerah Dalam Pengelolaan Wilayah Pesisir dan Pulau-Pulau Kecil - Sony, Edy (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: The regional authority to manage the resources of coastal areas of the sea and small islands as far as 12 miles for the province based on Law No. 9 of 2015 concerning the Second Amendment to Law No. 23 of 2014 concerning Regional Government causes horizontal conflicts of sea plots in the society. Not only conflicts between government institutions (sectoral conflicts) but also related to regional authorities in managing coastal marine resources and small islands. Purposes of the Research: To analyze various provisions of laws and regulations governing the authority of local governments in the management of coastal areas and small islands, as well as the role of local governments in the management of coastal areas and small islands. Methods of the Research: The type of research used is normative legal research that studies how legal norms are. The data collection method uses the library research. This study used secondary data obtained from various literature and regulations. Results of the Research: The results showed that since the enactment of Law Number 23 of 2014 concerning Regional Government, the authority to manage marine waters by the Regency / City Government has decreased. The zoning area as far as 0-4 miles which was originally managed by the Regency / City Government is now managed by the Provincial Government so as to make the zoning of the Provincial authority 0-12 miles. While the authority to manage sea areas more than 12 miles is carried out by the Central Government. In addition, the authority of Regional Governments in the management of coastal areas is also regulated in Law No. 1 of 2014 concerning amendments to Law No. 27 of 2007 concerning Management of Coastal Areas and Small Islands, Article 1 and Article 63 of Regional Governments organize government according to the principle of autonomy, which is a division of elective concurrent government affairs, where Regional Governments play an important role in community empowerment.